Analysis of Communicational Design and Information on University Websites - Barcellos, Livia Inglesis [UNESP]; Inglesis Barcellos, Ekaterina Emmanuil [UNESP]; Botura, Galdenoro [UNESP]; Ho, A. G. (Springer, 2018)
The Universities' websites get each day more importance by acting as a communication channel that offers the most different information, reaching users in large scale. Websites are usually the first contact with the institution, or source of relevant data. Its value goes beyond the initial intention and purpose, becoming a vital part of the University's personality. This article presents the outcome of a research made with 100 persons, where 85% having the most basic level of instructions, and 15% having Ph.D. title. The research sized people's first reactions by accessing websites of the five biggest and most renowned Universities around the world, according to international rankings. Data analysis was focused on identifying the support to people's expectations and needs, besides the facility of use, the interest aroused and respect to user's time, not mattering user's experience on using internet. The adoption of an unprecedented methodology that finds points where the interface designers must act to improve the usability and the results obtained showed the existence of a big field to be improved by websites designers when the focus of this communication channel is the user.
Keywords: Visual communication and design; Websites; Universities; ICT (Information and Communications Technology)